2008
DOI: 10.1542/peds.2008-1315c
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices Study II: Study Methods

Abstract: OBJECTIVE. Our goal is to describe the methods used in the Infant Feeding Practices Study II (IFPS II), a study of infant feeding and care practices throughout the first year of life. Survey topics included breastfeeding, formula and complementary feeding, infant health, breast-pump use, food allergies, sleeping arrangements, mother's employment, and child care arrangements. In addition, mothers' dietary intake was measured prenatally and postnatally.PARTICIPANTS AND METHODS. The IFPS II sample was drawn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
402
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 359 publications
(410 citation statements)
references
References 20 publications
2
402
1
1
Order By: Relevance
“…Detailed information on this survey administration and data collection have been previously published. 21 A total of 1542 children who participated in both IFPS II and a Year 6 FollowUp (Y6FU) survey in 2012 were included. About half (48%) of the children who participated in the original survey were lost to follow-up at 6 years of age.…”
Section: Study Population and Survey Administrationmentioning
confidence: 99%
“…Detailed information on this survey administration and data collection have been previously published. 21 A total of 1542 children who participated in both IFPS II and a Year 6 FollowUp (Y6FU) survey in 2012 were included. About half (48%) of the children who participated in the original survey were lost to follow-up at 6 years of age.…”
Section: Study Population and Survey Administrationmentioning
confidence: 99%
“…18,19 The IFPS II followed mothers and infants from late pregnancy through 1 year postpartum to understand infant feeding patterns, infants' health, factors that may affect infant feeding, and mothers' health and diet. Data were collected from May 2005 through June 2007 by using a nationally distributed consumer opinion panel.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…Duration of exclusive breastfeeding was not asked directly; therefore, exclusive breastfeeding duration was calculated by estimating the midpoint between the infant' s age on the last questionnaire in which the mother indicated exclusive breastfeeding and the infant's age on the first questionnaire in which she indicated that she was not exclusively breastfeeding. 18 Our predictor variable, breastfeeding duration, combined the overall and exclusive breastfeeding duration composite variables and was categorized as follows: never breastfed, breastfed ,6 months, breastfed $6 months but exclusively breastfed ,3 months, and breastfed $6 months and exclusively breastfed $3 months.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…The 3 solid food groups were meat or meat substitutes (meat/chicken, fish, peanuts, eggs, soy foods), fruits or vegetables (not including juice), and cereals (including infant cereal and other cereals/ starches). We then created the following 8 categories of food consumption: (1) 3 groups of solids consumed at least once per day; (2) 2 groups of solids consumed at least once per day; (3) 1 group of solids consumed at least once per day; (4) some solids consumed but no group consumed at least once per day; (5) liquids other than breast milk or formula but no solids consumed; (6) only breast milk and formula consumed; (7) only formula consumed; and (8) only breast milk consumed.…”
Section: Dietary Varietymentioning
confidence: 99%